New application of anti-TLR monoclonal antibodies: detection, inhibition and protection - Ryutaro Fukui; Yusuke Murakami; Kensuke Miyake (BMC, 2018)
Abstract Monoclonal antibody (mAb) is an essential tool for the analysis in various fields of biology. In the field of innate immunology, mAbs have been established and used for the study of Toll-like receptors (TLRs), a family of pathogen sensors that induces cytokine production and activate immune responses. TLRs play the role as a frontline of protection against pathogens, whereas excessive activation of TLRs has been implicated in a variety of infectious diseases and inflammatory diseases. For example, TLR7 and TLR9 sense not only pathogen-derived nucleic acids, but also self-derived nucleic acids in noninfectious inflammatory diseases such as systemic lupus erythematosus (SLE) or hepatitis. Consequently, it is important to clarify the molecular mechanisms of TLRs for therapeutic intervention in these diseases. For analysis of the molecular mechanisms of TLRs, mAbs to nucleic acid-sensing TLRs were developed recently. These mAbs revealed that TLR7 and TLR9 are localized also in the plasma membrane, while TLR7 and TLR9 were thought to be localized in endosomes and lysosomes. Among these mAbs, antagonistic mAbs to TLR7 or TLR9 are able to inhibit in vitro responses to synthetic ligands. Furthermore, antagonistic mAbs mitigate inflammatory disorders caused by TLR7 or TLR9 in mice. These results suggest that antagonistic mAbs to nucleic acid-sensing TLRs are a promising tool for therapeutic intervention in inflammatory disorders caused by excessive activation of nucleic acid-sensing TLRs. Here, we summarize the molecular mechanisms of TLRs and recent progresses in the trials targeting TLRs with mAbs to control inflammatory diseases.